EJAAN DALAM RUBRIK SURAT PEMBACA KOMPAS.COM - Destiani Destiani (Salingka, 2018)
This study focuses on orthographic problems occur on complaint letters posted on kompas.com on March 2017. The study used eighteen complaint letters.  The methodology is descriptive qualitative in order to describe the data as it is. The sampling technique was purposive. Analyisis technique for orthographic data includes steps such as: 1) data identification, 2) data classification and 3) improper spellings calculation. There are four categories of orthographic problems, they are: 1) use of alphabetic letters, 2) word typing, 3) punctuation and 4) word absorption. Results showed that 82 orthographic problems occured on three aspects.  The most dominant orthographic problem is word typing with 49 mistakes, followed by 19 alphabetic letter problems, 14 punctuation problems and zero for absorption problem. Keywords: orthography, complaint letters, word typing